High-Resolution Exposure Assessment for Volatile Organic Compounds in Two California Residences - Lunderberg, David M; Misztal, Pawel K.; Liu, YingJun; Arata, Caleb; Tian, Yilin; Kristensen, Kasper; Weber, Robert J; Nazaroff, William W.; Goldstein, Allen H (Environmental Science & Technology, 2021)
Time spent in residences substantially contributes to human exposure to volatile organic compounds (VOCs). Such exposures have been difficult to study deeply, in part because VOC concentrations and indoor occupancy vary rapidly. Using a fast-response online mass spectrometer, we report time-resolved exposures from multi-season sampling of more than 200 VOCs in two California residences. Chemical-specific source apportionment revealed that time-averaged exposures for most VOCs were mainly attributable to continuous indoor emissions from buildings and their static contents. Also contributing to exposures were occupant-related activities, such as cooking, and outdoor-to-indoor transport. Health risk assessments are possible for a subset of observed VOCs. Acrolein, acetaldehyde, and acrylic acid concentrations were above chronic advisory health guidelines, whereas exposures for other assessable species were typically well below the guideline levels. Studied residences were built in the mid-20th century, indicating that VOC emissions even from older buildings and their contents can substantially contribute to occupant exposures.